Analysis of the Relationship between the Utilization of Green Open Spaces (RTH) and the Level of Economic-Social Satisfaction of the Community in Mataram City - Haerul Anwar; ibrahim Ibrahim (Journal of Governance and Spatial Planning, 2025)
This study aims to analyze the relationship between the utilization of Green Open Spaces (RTH) and the socio-economic satisfaction of the community in Mataram City. RTH utilization was measured through visit frequency, types of activities, and duration of use, while socio-economic satisfaction included perceptions of economic benefits, social well-being, and surrounding environmental quality. A quantitative correlational approach was employed with 30 respondents selected through accidental sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and multiple linear regression. The findings indicate that both RTH utilization (X₁) and RTH quality/accessibility (X₂) have a positive and significant influence on socio-economic satisfaction (Y), with an R² value of 0.931. The strongest contribution comes from RTH quality/accessibility (B = 0.680), highlighting that facility conditions and accessibility play a crucial role in enhancing community well-being. These results suggest that optimizing social functions and the design quality of RTH can enhance urban socio-economic benefits. This study provides empirical insights for local governments in developing adaptive, inclusive, and community-oriented green spaces.